Qualitative review of dengue fever outbreak in dire Dawa City, Ethiopia, 2021: a thematic analysis approach - Yonas Assefa Tufa; Ibrahim Adulhamid; Negash Abera; Ahmed Mohammed; Yibeyin Mulualem; Mikiyas Alayu; Chalachew Sisay; Belay Makango; Ermiyas Woldie; Birhanu Regassa; Tsegaye Getachew; Mintesnot Hawaz; et al. (Taylor & Francis Group, 2023)
Abstract: In the past 15 years, there has been a dramatic increase in the global incidence of dengue and its severe manifestations, such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Epidemics in endemic countries are occurring more frequently with increasing magnitude. A well-managed front-line response not only reduces the number of unnecessary hospital admissions but also saves the lives of dengue patients. The objective of this study was to review the Dengue fever outbreak management in Dire Dawa City Administration Ethiopia, March 17_27,2021. The study employed a qualitative research approach, with thematic analysis. A purposive sampling method was used. Data were collected through FGDs, in-depth interviews, and document reviews. The results show there were qualified, experienced, and dedicated professionals for the management of the outbreak. In addition, the engagement of laboratory professionals to decrease the extent of outbreaks and to interrupt the rate of transmission was very interesting. However, the regional dengue fever laboratory investigation was limited to differential diagnosis because of the unavailability of diagnostic methods and essential laboratory equipment.